PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS DISCOVERY LEARNING PADA MATERI POLA BILANGAN KELAS VIII MTs - Annafi Sri Nanda (Departemen Matematika, 2021)
This study aims to develop learning media in the form of interactive multimedia learning based on discovery learning on valid and practical number pattern material. This type of research is a design research using the Plomp development model which is grouped into the preliminary research stage, the prototyping stage, and the assessment stage. The preliminary research phase includes needs analysis, student analysis, curriculum analysis, and material analysis. The prototyping stage is the stage of developing games-based multimedia learning on number pattern material. The prototype must go through evaluation with several stages in the form of self-evaluation and